The Voice of Science on Marine Biodiversity Negotiations: A Systematic Literature Review - Tessnow-von Wysocki, Ina; Vadrot, Alice B. M. (Frontiers in Marine Science, 2020)
Over one hundred governments are currently negotiating a new legally binding instrument for the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction (BBNJ). The new agreement is to address four broad themes: marine genetic resources (MGRs); area-based management tools (ABMTs), including marine protected areas (MPAs); environmental impact assessments (EIAs); and capacity building and the transfer of marine technology (CB&TT). Although a large corpus of scientific BBNJ literature exists, a comprehensive overview and critical analysis of the academic debate is currently missing. This systematic review seeks to fill this gap by examining the main priority topics and recommendations in a sample of 140 multidisciplinary, geographically diverse publications. As an up-to-date summary and analysis, it is intended for researchers from diverse academic disciplines in the natural and social sciences, policy-makers, and practitioners. It untangles the complex BBNJ negotiations, highlights the policy relevance of existing work, and facilitates links between science, policy, and practice. It presents recommendations made in the literature sample for each of the four package elements of the future treaty and identifies four overarching themes: ocean connectivity, institutional design, the role of science, and digital technology. This paper identifies two important gaps that need to be addressed if we are to conserve marine biodiversity in international waters: the science-policy interfaces and the need for transformative change.